Sans cesse redessiner les gestes d’émancipation - Nicolas Go (Recherches en Éducation)
This short contribution aims to be an introduction to the so often debated issue of pupil autonomy- not starting from the notion of autonomy itself, but from what I would like to suggest as possible conditions to its clarification, ie the principles of “authorization” (empowerment) and cooperation. Possible conditions that are not necessary, since these conditions refer back to those particular educational practices that I have been known to qualify as ‘cooperative complex’. Particular practices that are not without significance and that could even become a touchstone for the critique of the normalizing effects that imprudently persistent injunctions to pupil autonomy can paradoxically provoke. No doubt autonomy is the sign of an emancipation process in action. We still need to determine the real possibilities and describe the empirical effects. The joyful experience of work commonly shared could very well be- given specific requirements- a sign of the recognition of this process.